'A Friend in the Corner': supporting people at home in the last year of life via telephone and video consultation—an evaluation. Issue 4 (5th February 2016) - Middleton-Green, L; Gadoud, A; Norris, B; Sargeant, A; Nair, S; Wilson, L; Livingstone, H; Small, N
Abstract : Objective: To evaluate 'Gold Line', a 24/7, nurse-led telephone and video-consultation support service for patients thought to be in the last year of life in Bradford, Airedale, Wharfedale and Craven. Method: Data on the time and nature of all calls between 1 April 2014 and 30 March 2015 were obtained from the patient Electronic Records. Interviews with 13 participants captured patients and carers perspectives. Results: To date, 3291 patients have been referred to the Gold Line. During the study period, 42% of registered patients had a non-cancer diagnosis and 45.2% of service users were not known to Specialist Palliative Care services. The median time on the caseload was 49 days (range 1–504 days). 4533 telephone calls and 573 video consultations were made involving 1813 individuals. 39% of the 5106 contacts were resolved by the Gold Line team without referral to other services. 69% of calls were made outside normal working hours. Interviews with patients and carers reported experiences of support and reassurance from the Gold Line and the importance of practical advice was emphasised. Current data (year to October 2015) show that 98.5% of calls (4500/4568) resulted in patients remaining in their place of residence. Conclusions: A nurse led, 24/7 telephone and video consultation service can provide valuable support for patients identified to be in the last year of life and for their carers. The line enabled them to feel supported and remain in their place of residence, hence reducing the pressure for avoidable hospital admissions and use of other services. Providing this service may encourage healthcare professionals to identify more patients approaching the last year of life, widening support offered to this group of patients beyond those known to specialist palliative care services.